(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Every monthly event takes place in super market attached with pharmaceutical store with the single database attached in Bangalore city. The mall which we are working as the case study people around India, as Bangalore is the IT capital. As people stay far away from family, usually it is necessary to take all the things for the daily needs including grocery, pharmacy, ration and other commodities. As we know that India is a diverse country. People here in India has different ethnicity which is indirectly related to different language speaking population. Here we are making use of data to increase the sale of the store.